2019
DOI: 10.33369/jeet.3.1.42-52
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Students’ Listening Learning Style (A Study of the 5th Semester Students at English Education Study Program of Universitas Bengkulu in Academic Year 2018/2019)

Abstract: This research attemted to find out the learning style used in learning listening. This research was carried out by employing descriptive quantitative design. The population of this research was the fifth semester students of English Education Study Program of University of Bengkulu in academic year 2018/2019. The samples of this research were taken by using total sampling tehcnique, i.e 79 students. The data were collected by questionnaire consisted of 36 questions related to the learning style. The questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
2
5
1
Order By: Relevance
“…Therefore, Iranian learners in the study mainly paid attention to observation, and the analysis of issues, and they are inclined to think precisely before practically taking actions or making conclusions, which in turn are considered as special characteristics of reflectors. The study in this regard confirms the claims of Wulandari (2019) who concluded that learners have various learning behavior and styles which are motivated by their educational culture and personal experiences.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, Iranian learners in the study mainly paid attention to observation, and the analysis of issues, and they are inclined to think precisely before practically taking actions or making conclusions, which in turn are considered as special characteristics of reflectors. The study in this regard confirms the claims of Wulandari (2019) who concluded that learners have various learning behavior and styles which are motivated by their educational culture and personal experiences.…”
Section: Discussionsupporting
confidence: 87%
“…Hand (2000) also stated that this awareness is productive for learners and teachers equally. Wulandari (2019) have investigated the learning styles used in the listening comprehension at the university setting using a questionnaire adapted from Joy Reid. The findings suggest that there are generally three types of learning styles employed, namely, auditory, visual, and kinesthetic.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…As mentioned by Awla (2014), people have their own unique learning style and when they are able to identify their own learning style, it is easier for them to include techniques corresponding to their learning style into their learning process. The ability to listen is also mentioned before as the first skill to be mastered while learning to speak English (Wulandari, Harahap, & Hati, 2019). This thought might cause a misconception that auditory learners will be more fluent in English.…”
Section: Resultsmentioning
confidence: 95%
“…The first step that must be taken is listening, and it must be learned as early as possible. Listening skill is complicated as it is an intangible mental process (Wulandari, Harahap, & Hati, 2019). Therefore, concentration is particularly necessary.…”
Section: Introductionmentioning
confidence: 99%
“…By knowing the different learning styles of learners, educators will be better able to help them improve their academic capability efficiently (Saadi, 2012). They offer a systematic vision of how learners perceive and get involved with their learning situation (Wulandari, Harahap & Hati, 2019). Even though extensive academic studies have investigated language learning styles, yet, very little research has examined their role in specific language skills and there is also a gap in the literature on learning styles use among Iranian online EFL learners.…”
Section: Introductionmentioning
confidence: 99%